The need for social approval and the choice of gender-typed occupations - Eberhard, Verena [Verfasser]; Matthes, Stephanie [Verfasser]; Ulrich, Joachim Gerd [Verfasser] (My University, 2015)
"Human beings are dependent upon social approval to strengthen their identities. Therefore, they practice impression management: They anticipate which behaviour provokes which reactions in their social environment, and they tend to exhibit the kind of behaviour that promises positive feedback. Based on the assumption that human beings also show this behaviour in their choice of vocation, we hypothesise that young people are more likely to expect negative reactions from their social environment when choosing a gender-atypical occupation. Furthermore, we assume that the expected reaction of the social environment influences vocational orientation: The anticipation of negative reactions to gender-atypical vocational choice might contribute to explain why young people ignore this occupation. We tested both hypotheses with the help of data retrieved from a survey of young people in Germany who are interested in vocational education and training (VET). The results support our hypotheses; however, they also show that the relevance of a gender-typed vocational choice is weaker if adolescents have a higher educational background. In this case, the choice of an occupation that expresses a high educational status becomes more important. It may lead to an exclusive kind of social approval that is denied to people with a lower educational background." (Authors' abstract, BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; Berufswahlverhalten; Frauenberuf; Männerberuf; Soziokulturelle Faktoren